Bullous pemphigoid and multiple sclerosis: a report of three cases and review of the literature. - Kirtschig, G; Walkden, V; Venning, V; Wojnarowska, F (1995)
Three patients with longstanding multiple sclerosis (MS) who developed bullous pemphigoid (BP) are reported. All patients had immunological features of typical BP as determined by immunofluorescence and Western immunoblotting studies. The clinical features, however, differed from those observed in typical BP. In two the BP started near an indwelling catheter and two had striking involvement of the soles. None of our patients, or a further nine cases reported in the literature, had mucous membrane involvement. In MS patients BP appears to develop at a younger age. Multiple drugs were taken by the MS patients; these, however, appear not to play a role in triggering their BP. The course of BP in patients with MS is moderate, although the majority require systemic treatment.